A exigibilidade judicial do direito fundamental à educação na Constituição Federal de 1988 - LIMA, Isabela Bentes de (Universidade Federal do Pará, 2015)
The current study aims to analyze the effectiveness of the right to education in Brazilian 1988 Constitution. It intends to examine the concept, nature, costs (as the creation of a funding to FUNDEB and the designation on the percentage to be used for the maintenance and development of education by federal entities) the role of state and society, as well as constitutional principles that rule the implementation of the right to education in Brazil. Based on referential that the Social and Democratic State of Rights is protector of the social rights, it was relevant carefully taking into account the concepts of “existential minimum”, and scarcity of resources. Furthermore, this study analyzes two judgments of Supreme Court, phenomenon named by most of doctrine as “judicialization of public policies”, which are the cases Santo André / SP and Queimados/ RJ. Finally, these judgments are analyzed according to the principles and values that guide the Brazilian Constitution which led to the conclusion that the collective demands of supplying the right to education have priority over the individual demands, despite both of them being required.